Kristy ask Lonnie to think add 3 to it multiply the sum by 2 and the subtract 6 let n stand for lonnie starting number which expression represents Lonnie final number?



Respuesta :

Answer:

2(n+3)-6

n=0

Step-by-step explanation:

2(3+n)-6=

Simplifying

2(3 + n) + -6 = 0

(3 * 2 + n * 2) + -6 = 0

(6 + 2n) + -6 = 0

Reorder the terms:

6 + -6 + 2n = 0

Combine like terms: 6 + -6 = 0

0 + 2n = 0

2n = 0

Solving

2n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Divide each side by '2'.

n = 0

Simplifying

n = 0